Combining ability and gene action studies to select okra (Abelmoschus esculentus) inbred for carbohydrate, vitamins and antioxidant traits - DAS, ANJAN; YADAV, RAMESH KUMAR; BHARDWAJ, RAKESH; CHOUDHARY, HARSHWARDHAN; TALUKDAR, AKSHAY; KHADE, YOGESH P; CHANDEL, RAHUL (The Indian Journal of Agricultural Sciences, 2020)
Development of quality hybrids having better productivity as well as rich in major antioxidant and phytochemical compounds is a prime objective of any vegetable improvement program throughout the world. Okra (Abelmoschus esculentus (L.) Moench.), a member of the family malvaceae is a rich source of several minerals, vitamins and crude fiber. Thus, to exploit its nutritional potential in the form of hybrids selection involving right parents is the foremost criteria. With this aim, the present experiment was designed to know about the gene action for quality traits involving 10 lines and 3 testers in line × tester method. ANOVA revealed significance for all the traits. On the basis of both gca effect and per se performance, Pusa Bhindi-5 was regarded as the best parent for chlorophyll content (a and b), DOV- 92 for total carotenoids, Kashi Pragati for ascorbic acid and sugar content and Pusa Sawani for total phenol. Similarly, on the basis of both sca effect and per se performance, the cross Kashi Pragati × Pusa Bhindi-5 was found to be the best hybrid combination for chlorophyll a only, DOV- 1 × Pusa Bhindi- 5 for total carotenoids, Kashi Pragati × Pusa A-4 for ascorbic acid and DOV- 92 × Pusa Bhindi- 5 for antioxidant content of fruit. Analysis of degree of dominance and predictability ratio also indicated the presence of non-additive gene action for all the traits. In was concluded that parents which performed well for particular trait, possessed high potentiality for heterosis breeding program.